High-strength durable composite geomembrane and preparation method thereof

By using modified polybutadiene as an anti-aging additive and heat dissipation reinforcement in geomembrane, the problems of low mechanical strength and poor durability of geomembrane are solved, and the high strength, wear resistance and long-term anti-aging effects of geomembrane are achieved.

CN119704789AActive Publication Date: 2025-03-28SHANDONG YIBO SUNSHINE ENG MATERIALS CO LTD

Patent Information

Application Number
CN202411778221.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-28
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

The existing geomembrane has low mechanical strength, and its impact resistance and aging resistance are average, resulting in poor durability and difficult to meet the requirements of long-term civil engineering.

Method used

A high-strength and durable composite geomembrane consisting of a nonwoven fiber fabric layer and a substrate layer is used. Modified polybutadiene is added to the substrate layer as an anti-aging additive and a heat-dissipation reinforcement filler to enhance the toughness, impact resistance and anti-aging effect of the geomembrane.

Benefits of technology

It significantly improves the mechanical strength, wear resistance and impact resistance of geomembrane, extends its service life, and enhances its durability in complex environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119704789A_ABST
    Figure CN119704789A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of geomembranes, and discloses a high-strength durable composite geomembrane and a preparation method thereof.The high-strength durable composite geomembrane is composed of a non-woven fiber cloth layer and a base material layer; wherein the base material layer comprises the following raw materials: linear low-density polyethylene, high-density polyethylene, an anti-aging additive, a heat dissipation reinforcing filler, a dispersing agent, an initiator and a flame retardant; the anti-aging additive and the heat dissipation reinforcing filler are prepared and added into the preparation process of the geomembrane base material layer, so that the prepared geomembrane has excellent mechanical strength, wear resistance and impact resistance and also has a long-term anti-aging effect, the durability of the geomembrane is remarkably enhanced, and the service life of the geomembrane is prolonged. And the use requirements in long-term engineering in various complex environments can be met, and the service life is long.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of geomembranes, and in particular to a high-strength and durable composite geomembrane and a preparation method thereof. Background Art

[0002] Geomembrane is a barrier material made of polymer materials through extrusion, stretching and other processes. It is widely used in engineering fields such as water conservancy, transportation, agriculture, and environment. It is an indispensable and important part of modern engineering construction. Due to the wide use of geomembranes, they need to face complex use environments. Therefore, geomembranes need to have the ability to maintain stable performance in ultraviolet and high temperature environments, and have good anti-aging effects, so as to adapt to the use requirements of engineering sites. At the same time, they also need to have excellent mechanical strength and good impact resistance, so that the geomembrane is not easily damaged when impacted, and can play a better and longer-lasting anti-seepage role.

[0003] Nowadays, with the continuous development of industrial technology, the durability of ordinary geomembranes is generally average and it is difficult to meet the requirements of long-term civil engineering use in complex environments. Therefore, in actual use, they are usually improved. For example, the patent with announcement number CN104592691B announces a plastic geotextile and a preparation method thereof. The plastic geotextile has good mechanical strength and strong impact resistance, and is made of recycled waste PVC, which greatly reduces production costs and reduces environmental pollution. It can bring good economic benefits and has the value of promotion and application. However, the geomembrane prepared by this patent directly adds antioxidants during the preparation process. When used in long-term projects, small molecule antioxidants have the risk of precipitation, which leads to a decrease in the anti-aging ability of the geotextile and affects the service life of the geotextile. Summary of the invention

[0004] The purpose of the present invention is to provide a high-strength and durable composite geomembrane and a preparation method thereof, which solves the technical problem that ordinary geomembranes have low mechanical strength, poor impact resistance and anti-aging ability, which generally lead to poor durability and are difficult to meet the long-term use requirements of civil engineering.

[0005] The purpose of the present invention can be achieved through the following technical solutions: A high-strength and durable composite geomembrane consists of two parts: a non-woven fiber cloth layer and a substrate layer; the substrate layer comprises the following raw materials in parts by weight: 25-35 parts of linear low-density polyethylene, 30-40 parts of high-density polyethylene, 8-10 parts of anti-aging additives, 5-6 parts of heat dissipation enhancing fillers, 1-3 parts of dispersants, 1.5-2.5 parts of initiators, and 2-5 parts of flame retardants.

[0006] Furthermore, the dispersant is any one of polyethylene wax, stearic acid, and paraffin; the initiator is any one of dicumyl peroxide and benzoyl peroxide; and the flame retardant is any one of flame retardant DDP and flame retardant DOPO.

[0007] Furthermore, the preparation method of the anti-aging aid comprises the following steps: S1: placing epoxidized polybutadiene in toluene, adding 3,5-di-tert-butyl-4-hydroxybenzoic acid and tetrabutylammonium bromide, heating to 65-70° C. for reaction for 5-6 hours, and collecting the product after reduced pressure distillation to obtain modified polybutadiene; S2: Place modified polybutadiene and brominated maleic anhydride in xylene, mix thoroughly, add a catalyst, heat to 55-65°C and react for 8-10 hours, collect the product after reduced pressure distillation, and obtain an anti-aging additive.

[0008] In this scheme, under the action of tetrabutylammonium bromide, the epoxy groups at both ends of the epoxidized polybutadiene structure react with the carboxyl groups in the 3,5-di-tert-butyl-4-hydroxybenzoic acid structure to obtain a modified polybutadiene containing hindered phenol groups and active hydroxyl groups at both ends. Then, under the action of a catalyst, the active hydroxyl groups in the modified polybutadiene structure react with the active bromine in the brominated maleic anhydride structure to obtain an anti-aging additive. This anti-aging additive is added to the preparation process of the geomembrane. The polybutadiene chain segments in its structure can effectively enhance the toughness of the geomembrane and improve the Impact resistance: the hindered phenol groups in its structure are connected to the molecular chain of the anti-aging additive in a chemically bonded manner, which can effectively prevent the migration of small molecule hindered phenol groups during long-term use of the geomembrane, thereby affecting the durability of the anti-aging effect, and making the geomembrane have excellent and long-lasting anti-aging ability. At the same time, maleic anhydride groups are also connected to both ends of the molecular chain of this anti-aging additive, which can interact with the geomembrane matrix material during the production process, thereby improving the structural density of the geomembrane matrix material, enhancing the mechanical strength of the geomembrane, and significantly enhancing the service life of the geomembrane.

[0009] Furthermore, in step S1, the epoxy content of the epoxidized polybutadiene is 2.5%-4.0%.

[0010] Furthermore, in step S2, the catalyst is potassium carbonate.

[0011] Furthermore, the preparation method of the heat dissipation enhancing filler comprises the following steps: SS1: titanium dioxide is placed in anhydrous ethanol, ultrasonically dispersed for 10-15 minutes, ammonia water is added to adjust the pH to 9-10, isocyanatepropyltriethoxysilane is added, reacted in a water bath at 80-85°C for 2-3 hours, filtered, washed, and vacuum dried to obtain modified titanium dioxide; SS2: The modified titanium dioxide and boron nitride nanosheets are placed in N,N-dimethylformamide, ultrasonically dispersed for 15-20 minutes, and then dibutyltin dilaurate is added. The temperature is raised to react, and the heat dissipation enhancing filler is obtained after filtering, washing, and vacuum drying.

[0012] In this scheme, under the regulation of ammonia water, the silaneoxy groups in the structure of isocyanatepropyltriethoxysilane react with the hydroxyl groups on the surface of titanium dioxide to obtain a modified titanium dioxide with an isocyanate group on the surface, and then under the action of dibutyltin dilaurate, the isocyanate groups on the surface of the modified titanium dioxide react with the hydroxyl groups on the surface of the boron nitride nanosheets to obtain a heat dissipation enhancing filler; the heat dissipation enhancing filler uses isocyanatepropyltriethoxysilane as a bridging agent to connect the granular titanium dioxide and the boron nitride nanosheets with a lamellar structure to form a heat dissipation enhancing filler. The micro-ball effect can not only improve the dispersion of heat-dissipating enhancing fillers in the matrix, but also enhance the wear resistance and mechanical strength of the geomembrane. At the same time, titanium dioxide has excellent UV resistance and can produce a synergistic effect with anti-aging additives to enhance the anti-aging ability of the geomembrane and the durability of the geomembrane. Boron nitride nanosheets have a layered structure and excellent heat dissipation ability. They can dissipate heat in time in high temperature environments in summer, reduce the impact of high temperature environments on the geomembrane structure, enhance the anti-aging ability of the geomembrane, and effectively extend the service life of the geomembrane.

[0013] Furthermore, in step SS1, the concentration of the ammonia water is 2-3 mol / L.

[0014] Furthermore, in step SS2, the temperature of the temperature-raising reaction is 75-85° C., and the time is 3-5 hours.

[0015] A method for preparing a high-strength and durable composite geomembrane comprises the following steps: Step 1: Place linear low-density polyethylene, high-density polyethylene, anti-aging additive, dispersant, initiator, and flame retardant in an internal mixer, and blend at 115-125° C. for 15-20 minutes to obtain a mixture; Step 2: placing the mixed material in a twin-screw extruder, adding heat dissipation enhancing filler, setting the screw speed to 200-300 r / min, the extrusion temperature to 180-200° C., and calendering after melt extrusion to obtain a substrate layer; Step 3: Lay the nonwoven fiber cloth flat, place the substrate layer, and compact and compound the substrate layer and the nonwoven fiber cloth by ultrasonic pressing technology to obtain a composite geomembrane.

[0016] Beneficial effects of the present invention: The present invention prepares anti-aging additives and heat dissipation enhancing fillers and adds them to the preparation process of geomembrane, so that the prepared geomembrane has excellent mechanical strength, wear resistance, impact resistance, and long-term anti-aging effect, which significantly enhances the durability of the geomembrane, enables it to meet the use requirements of long-term projects in a variety of complex environments, and has a long service life.

[0017] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0019] Figure 1 It is the thermal weight loss curve of titanium dioxide, modified titanium dioxide and heat dissipation enhancing filler in the present invention. DETAILED DESCRIPTION

[0020] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] The preparation methods of the anti-aging additives and heat dissipation enhancing fillers in the following examples and comparative examples of the present invention are as follows: 1. Preparation of anti-aging additives S1: 2.6 g of epoxidized polybutadiene with an epoxy content of 3.5% was placed in 50 ml of toluene, 2 g of 3,5-di-tert-butyl-4-hydroxybenzoic acid and 0.06 g of tetrabutylammonium bromide were added, the temperature was raised to 65° C. and reacted for 5 h, and the product was collected after reduced pressure distillation to obtain modified polybutadiene; The content of hydroxyl groups in modified polybutadiene was tested by titration. The specific method was as follows: 1 g of modified polybutadiene was weighed as a sample for use, 100 ml of ethyl acetate reagent, 1.5 ml of 70% perchloric acid and 5 ml of acetic anhydride were mixed, and the mixture was placed in a water bath at 15°C for 30 min, and then 25 ml of acetic anhydride reagent was added, and the mixture was shaken to prepare an acylation reagent for use, 30 ml of pyridine was placed in 10 ml of distilled water, and the mixture was shaken to prepare a hydrolysis reagent for use, the sample was placed in a titration bottle, 10 ml of ethyl acetate reagent and 3 ml of acetylation reagent were added, and the reaction was fully reacted for 25 min, then 2 ml of distilled water was added ... 5 ml of hydrolysis reagent was added, and the mixture was allowed to stand for 10 mi n, add 3 drops of phenolphthalein indicator, titrate with 1mol / L standard potassium hydroxide titration solution to the reaction endpoint, and perform a blank experiment at the same time. Calculate the hydroxyl value of the sample according to the following formula; Hydroxyl value (mgKOH / g) = (V-V1) × 56.11 × C / m; where V is the volume of standard potassium hydroxide titration solution consumed in the blank experiment, ml; V1 is the volume of standard potassium hydroxide titration solution consumed by the sample in the experiment, ml; 56.11 is the molar mass fraction of potassium hydroxide, g / mol; C is the actual molar concentration of the standard titration solution, 1mol / L; m is the sample mass, g; After calculation, the hydroxyl value of the modified polybutadiene is 35.25mgKOH / g.

[0022] S2: 3 g of modified polybutadiene and 2.5 g of bromomaleic anhydride were placed in 60 ml of xylene, mixed thoroughly, and then 0.1 g of potassium carbonate was added. The mixture was heated to 55°C and reacted for 8 h. The product was collected after reduced pressure distillation to obtain an anti-aging agent.

[0023] The hydroxyl content in the anti-aging agent is tested by titration. The specific testing method is the same as step S1. After calculation, the hydroxyl value content in the anti-aging agent is 9.31 mgKOH / g. The reduction in the hydroxyl content is due to the reaction between the active hydroxyl groups in the modified polybutadiene structure and the active bromine in the brominated maleic anhydride structure.

[0024] 2. Preparation of heat dissipation enhancing filler SS1: 2.8 g of titanium dioxide was placed in 100 ml of anhydrous ethanol, and ultrasonically dispersed for 10 min. Ammonia water with a concentration of 2 mol / L was added to adjust the pH to 9. 2 g of isocyanatepropyltriethoxysilane was added, and the mixture was reacted in a water bath at 80° C. for 2 h. The modified titanium dioxide was obtained after filtering, washing, and vacuum drying. SS2: 3 g of modified titanium dioxide and 2.5 g of boron nitride nanosheets were placed in 180 ml of N,N-dimethylformamide, and after ultrasonic dispersion for 15 min, 0.2 g of dibutyltin dilaurate was added, and the temperature was raised to 75 °C for reaction for 3 h. After filtering, washing, and vacuum drying, a heat dissipation enhancing filler was obtained.

[0025] The same mass of titanium dioxide, modified titanium dioxide and heat dissipation enhancing filler were used as samples for thermogravimetric analysis. Figure 1 It is a thermal weight loss curve, which is calculated by the following formula: m%=m1-m2; where m% is the sample weight loss rate; m1 is the initial mass fraction of the sample, %; m2 is the mass fraction of the sample after thermal weight loss, %. Calculation shows that the weight loss rate of titanium dioxide is 2.1%, and the lost part is caused by the thermal decomposition of crystalline water in the structure; the weight loss rate of modified titanium dioxide is 43.8%, and the lost part is caused by the thermal decomposition of isocyanatepropyltriethoxysilane coated on the surface of titanium dioxide; the weight loss rate of the heat dissipation enhancing filler is 24.8%, and the lost part is caused by the thermal decomposition of crystalline water and organic matter in the heat dissipation enhancing filler. Example

[0026] Preparation of composite geomembrane Step 1: put 25g of linear low-density polyethylene, 30g of high-density polyethylene, 8g of anti-aging additive, 1g of polyethylene wax, 1.5g of diisopropyl peroxide, and 2g of flame retardant DDP in a mixer, and blend at 115°C for 15min to obtain a mixture; Step 2: Place the mixed material in a twin-screw extruder, add 5g of heat dissipation enhancing filler, set the screw speed to 200r / min, the extrusion temperature to 180°C, and calender after melt extrusion to obtain a substrate layer; Step 3: Lay the nonwoven fiber cloth flat, place the substrate layer, and compact and compound the substrate layer and the nonwoven fiber cloth by ultrasonic pressing technology to obtain a composite geomembrane. Example

[0027] Preparation of composite geomembrane Step 1: Place 30 g of linear low-density polyethylene, 35 g of high-density polyethylene, 9 g of anti-aging agent, 2 g of stearic acid, 2 g of benzoyl peroxide, and 3.5 g of flame retardant DOPO in a mixer, and blend at 120° C. for 18 min to obtain a mixture; Step 2: Place the mixed material in a twin-screw extruder, add 5.5 g of heat dissipation enhancing filler, set the screw speed to 250 r / min, and the extrusion temperature to 190° C., and perform calendering after melt extrusion to obtain a substrate layer; Step 3: Lay the nonwoven fiber cloth flat, place the substrate layer, and compact and compound the substrate layer and the nonwoven fiber cloth by ultrasonic pressing technology to obtain a composite geomembrane. Example

[0028] Preparation of composite geomembrane Step 1: Place 35 g of linear low-density polyethylene, 40 g of high-density polyethylene, 10 g of an anti-aging agent, 3 g of paraffin, 2.5 g of diisopropyl peroxide, and 5 g of a flame retardant DDP in a mixer and blend at 125° C. for 20 min to obtain a mixture; Step 2: Place the mixed material in a twin-screw extruder, add 6 g of heat dissipation enhancing filler, set the screw speed to 300 r / min, the extrusion temperature to 200° C., and calender after melt extrusion to obtain a substrate layer; Step 3: Lay the nonwoven fiber cloth flat, place the substrate layer, and compact and compound the substrate layer and the nonwoven fiber cloth by ultrasonic pressing technology to obtain a composite geomembrane.

[0029] Comparative Example 1 Preparation of composite geomembrane Step 1: Place 30 g of linear low-density polyethylene, 35 g of high-density polyethylene, 9 g of anti-aging agent, 2 g of stearic acid, 2 g of benzoyl peroxide, and 3.5 g of flame retardant DOPO in a mixer, and blend at 120° C. for 18 min to obtain a mixture; Step 2: placing the mixed material in a twin-screw extruder, setting the screw speed to 250 r / min, the extrusion temperature to 190° C., and calendering after melt extrusion to obtain a substrate layer; Step 3: Lay the nonwoven fiber cloth flat, place the substrate layer, and compact and compound the substrate layer and the nonwoven fiber cloth by ultrasonic pressing technology to obtain a composite geomembrane.

[0030] Comparative Example 2 Preparation of composite geomembrane Step 1: Place 30 g of linear low-density polyethylene, 35 g of high-density polyethylene, 2 g of stearic acid, 2 g of benzoyl peroxide, and 3.5 g of flame retardant DOPO in a mixer and blend at 120° C. for 18 min to obtain a mixture; Step 2: Place the mixed material in a twin-screw extruder, add 5.5 g of heat dissipation enhancing filler, set the screw speed to 250 r / min, and the extrusion temperature to 190° C., and perform calendering after melt extrusion to obtain a substrate layer; Step 3: Lay the nonwoven fiber cloth flat, place the substrate layer, and compact and compound the substrate layer and the nonwoven fiber cloth by ultrasonic pressing technology to obtain a composite geomembrane.

[0031] Comparative Example 3 Preparation of composite geomembrane Step 1: 30 g of linear low-density polyethylene, 35 g of high-density polyethylene, 9 g of modified polybutadiene, 2 g of stearic acid, 2 g of benzoyl peroxide, and 3.5 g of flame retardant DOPO were placed in an internal mixer and blended at 120° C. for 18 min to obtain a mixture; Step 2: Place the mixed material in a twin-screw extruder, add 5.5 g of heat dissipation enhancing filler, set the screw speed to 250 r / min, and the extrusion temperature to 190° C., and perform calendering after melt extrusion to obtain a substrate layer; Step 3: Lay the nonwoven fiber cloth flat, place the substrate layer, and compact and compound the substrate layer and the nonwoven fiber cloth by ultrasonic pressing technology to obtain a composite geomembrane.

[0032] Comparative Example 4 Preparation of composite geomembrane Step 1: Place 30 g of linear low-density polyethylene, 35 g of high-density polyethylene, 9 g of anti-aging agent, 2 g of stearic acid, 2 g of benzoyl peroxide, and 3.5 g of flame retardant DOPO in a mixer, and blend at 120° C. for 18 min to obtain a mixture; Step 2: Place the mixture in a twin-screw extruder, add 5.5 g of titanium dioxide, set the screw speed to 250 r / min, and the extrusion temperature to 190° C., and perform calendering after melt extrusion to obtain a substrate layer; Step 3: Lay the nonwoven fiber cloth flat, place the substrate layer, and compact and compound the substrate layer and the nonwoven fiber cloth by ultrasonic pressing technology to obtain a composite geomembrane.

[0033] Comparative Example 5 Preparation of composite geomembrane Step 1: Place 30 g of linear low-density polyethylene, 35 g of high-density polyethylene, 9 g of anti-aging agent, 2 g of stearic acid, 2 g of benzoyl peroxide, and 3.5 g of flame retardant DOPO in a mixer, and blend at 120° C. for 18 min to obtain a mixture; Step 2: Place the mixture in a twin-screw extruder, add 5.5 g of boron nitride nanosheets, set the screw speed to 250 r / min, the extrusion temperature to 190° C., and perform calendering after melt extrusion to obtain a substrate layer; Step 3: Lay the nonwoven fiber cloth flat, place the substrate layer, and compact and compound the substrate layer and the nonwoven fiber cloth by ultrasonic pressing technology to obtain a composite geomembrane.

[0034] Performance Testing The substrate layers prepared in Examples 1 to 3 and Comparative Examples 1 to 5 were made into samples that met the specifications using a universal sample preparation machine. The samples, the samples treated in an aging box at 80°C for 72 hours, and the samples treated in a UV aging box with an irradiance of 0.72 / m2 for 48 hours were tested for tensile strength according to the reference standard GB / T1043.3-2006; the samples were tested for impact strength according to the reference standard GB / T1043-2008; the thermal conductivity of the samples was tested using a DZDR-S thermal conductivity tester; the wear resistance of the samples was tested using a Taber abrasion tester, two grinding wheels were placed on the samples, the grinding wheel speed was set to 30r / min, and the samples were subjected to a wear test, the initial mass of the samples, and the mass of the samples after 2000r of wear were recorded, and the sample wear value was calculated by referring to the formula wear value = initial mass of the sample - mass of the sample after wear; the specific test results are shown in the table below:

[0035] It can be seen from the above table that the substrate layers prepared in Examples 1 to 3 all have excellent mechanical strength, good wear resistance, excellent heat aging resistance and UV aging resistance, strong impact resistance, and good heat dissipation performance. After being compounded with non-woven fiber cloth, they can meet the use requirements of geotextiles in various environments, have a long service life and excellent durability. However, in the sample prepared in Comparative Example 1, no heat dissipation enhancing filler was added, and the heat dissipation performance was average. In the sample prepared in Comparative Example 2, no anti-aging additive was added, and the heat aging resistance was not strong. In the sample prepared in Comparative Example 3, modified polybutadiene was directly added, and no anti-aging additive was added. In the sample prepared in Comparative Example 4, no heat dissipation enhancing filler was added, and titanium dioxide was directly added. In the sample prepared in Comparative Example 5, no heat dissipation enhancing filler was added, and boron nitride was directly added. It can be seen that the samples prepared in the comparative examples are not as good as the embodiments in performance.

[0036] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0037] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the scope defined by the concept of the invention, they should all fall within the protection scope of the present invention.

Claims

1. A high-strength and durable composite geomembrane, characterized in that: The invention consists of two parts: a non-woven fiber cloth layer and a substrate layer; the substrate layer comprises the following raw materials in parts by weight: 25-35 parts of linear low-density polyethylene, 30-40 parts of high-density polyethylene, 8-10 parts of anti-aging additives, 5-6 parts of heat dissipation enhancing fillers, 1-3 parts of dispersants, 1.5-2.5 parts of initiators, and 2-5 parts of flame retardants.

2. A high-strength and durable composite geomembrane according to claim 1, characterized in that: The dispersant is any one of polyethylene wax, stearic acid, and paraffin; the initiator is any one of dicumyl peroxide and benzoyl peroxide; and the flame retardant is any one of flame retardant DDP and flame retardant DOPO.

3. The high-strength and durable composite geomembrane according to claim 1, characterized in that: The preparation method of the anti-aging aid comprises the following steps: S1: placing epoxidized polybutadiene in toluene, adding 3,5-di-tert-butyl-4-hydroxybenzoic acid and tetrabutylammonium bromide, heating to 65-70° C. for reaction for 5-6 hours, and collecting the product after reduced pressure distillation to obtain modified polybutadiene; S2: Place modified polybutadiene and brominated maleic anhydride in xylene, mix thoroughly, add a catalyst, heat to 55-65°C and react for 8-10 hours, collect the product after reduced pressure distillation, and obtain an anti-aging additive.

4. A high-strength and durable composite geomembrane according to claim 3, characterized in that: In step S1, the epoxy content of the epoxidized polybutadiene is 2.5%-4.0%.

5. The high-strength and durable composite geomembrane according to claim 3, characterized in that: In step S2, the catalyst is potassium carbonate.

6. The high-strength and durable composite geomembrane according to claim 1, characterized in that: The preparation method of the heat dissipation enhancing filler comprises the following steps: SS1: titanium dioxide is placed in anhydrous ethanol, ultrasonically dispersed for 10-15 minutes, ammonia water is added to adjust the pH to 9-10, isocyanatepropyltriethoxysilane is added, reacted in a water bath at 80-85°C for 2-3 hours, filtered, washed, and vacuum dried to obtain modified titanium dioxide; SS2: The modified titanium dioxide and boron nitride nanosheets are placed in N,N-dimethylformamide, ultrasonically dispersed for 15-20 minutes, and then dibutyltin dilaurate is added. The temperature is raised to react, and the heat dissipation enhancing filler is obtained after filtering, washing, and vacuum drying.

7. The high-strength and durable composite geomembrane according to claim 6, characterized in that: In step SS1, the concentration of the ammonia water is 2-3 mol / L.

8. The high-strength and durable composite geomembrane according to claim 6, characterized in that: In step SS2, the temperature of the temperature-raising reaction is 75-85° C. and the time is 3-5 h.

9. A method for preparing a high-strength and durable composite geomembrane as claimed in claim 1, characterized in that: The following steps are involved: Step 1: Place linear low-density polyethylene, high-density polyethylene, anti-aging additive, dispersant, initiator, and flame retardant in an internal mixer, and blend at 115-125° C. for 15-20 minutes to obtain a mixture; Step 2: placing the mixed material in a twin-screw extruder, adding heat dissipation enhancing filler, setting the screw speed to 200-300 r / min, the extrusion temperature to 180-200° C., and calendering after melt extrusion to obtain a substrate layer; Step 3: Lay the nonwoven fiber cloth flat, place the substrate layer, and compact and compound the substrate layer and the nonwoven fiber cloth by ultrasonic pressing technology to obtain a composite geomembrane.

Citation Information

Patent Citations

  • A kind of plastic geotextile and preparation method thereof

    CN104592691B

  • High-strength puncture-resistant geomembrane as well as preparation method and application thereof

    CN112029185A

  • Preparation method of long-acting anti-aging material

    CN114573495A

  • Anti-aging PVC composite material

    CN118256045A

Cited By

  • Anti-ultraviolet waterproof cloth

    CN122008662A